Rainfall extremes explain interannual shifts in timing and synchrony of calving in topi and warthog - Ogutu, Joseph O.; Piepho, Hans-Peter; Dublin, H.T.; Bhola, N.; Reid, Robin S. (Wiley, 2010)
We tested the hypothesis that ungulates time and synchronize births to match gestation and lactation with peak food availability and quality in seasonal environments, using ground counts of topi and warthog conducted over 174 months (July 1989–December 2003) in the Mara–Serengeti ecosystem. During this 15-year period, 2,725 newborn and 45,574 adult female topi and 933 newborn and 7,831 adult warthogs were recorded. Births were distinctly synchronized in both species but far less so than in ungulates in temperate regions. Extreme droughts delayed onset and reduced synchrony of calving and natality rates but high rainfall advanced onset and increased synchrony of calving and natality rates in both species, supporting the seasonality hypothesis. Annual shifts in birth peaks were significantly negatively correlated with the preceding wet season rainfall. Varying the timing and synchrony of births and natality rates are widespread but little understood adaptations of ungulates to climatic extremes. Climate change heightens the need for advancing this understanding because increasing frequency and severity of droughts is likely to decouple phenology of breeding in seasonally breeding ungulates from that in their food plants. Similar studies of African ungulates are either extremely rare or non-existent. New approaches to estimating the time of peak births and its confidence limits and the degree of synchrony of breeding are also presented.